PERLINDUNGAN HUKUM BAGI PEMBELI TERHADAP PERALIHAN HAK ATAS TANAH AKIBAT JUAL BELI YANG DILAKUKAN DI BAWAH TANGAN - Ulfah, T Sy Alfina; Wira Franciska,; Amelia Nur Widyanti, (Journal of Innovation Research and Knowledge, 2025)
This research discusses legal issues arising from the practice of unregistered land rights transactions. This practice is often conducted to avoid administrative fees, expedite the transaction process, or due to a lack of knowledge of applicable legal procedures. Unregistered transactions do not meet formal legal requirements and thus have the potential to cause problems, such as when the seller or their heirs deny the existence of the transaction, or when the land becomes the subject of a dispute in court. This causes good faith purchasers to face difficulty in defending their rights because the evidence they possess lacks probative value. The theories used in this research are the Theory of Legal Consequences by Soeroso and the Theory of Legal Protection by Satjipto Rahardjo. The research method used is normative legal research, which is conducted by examining library materials or secondary data. The approaches used in this study include the statute approach to examine all relevant laws and regulations, the case approach to build legal arguments based on concrete cases, the analytical approach, and the conceptual approach. The legal materials used consist of primary legal materials that are authoritative and binding, secondary legal materials, and tertiary legal materials. Based on an analysis of court decisions, it was found that the Indonesian justice system seeks to provide legal protection to good faith purchasers in unregistered land transactions. Although the transaction was not made before a competent official, the court can declare the sale and purchase valid and establish the buyer as the legal owner. This indicates that ownership of land rights does not only depend on the PPAT deed, but also on strong evidence of the agreement, full payment, and legal physical possession.